Systematic Review : Immunoglobulin Concentration in Breast Milk as a Body Defense against Sars-Cov-2 - Miftah Chairunnisa; Ananti Setya P P; Dewi Rahmawaty A P (STIKes Patria Husada Blitar, 2021)
The largest cases of pneumonia occurred in Wuhan City, Hubei Province of China in December 2019, which resembles SARS-CoV as a cause of SARS (Severe Acute Respiratory Syndrome) virus infection. The number of cases reaches 3.2 million people worldwide, and among them are breastfeeding mothers. Although virus transmission occurs through direct contact with infected patients, the number of infants or young children who were infected with COVID-19 during breastfeeding was only 10%. There is no scientific evidence for vertical transmission from mother to her baby during pregnancy and breastfeeding. The content of immunoglobulin A (IgA), immunoglobulin M (IgM), and immunoglobulin G (IgG) has a positive impact on the infant’s body. The objective of the study was to determine the immunoglobulin concentration in breast milk against SARS CoV2. The method used a systematic review approach with the design of Preferred Reporting Items For Systematic Reviews & Meta-Analyses (PRISMA). The result showed laboratory clinical trials, the IgA, IgG, and IgM responses showed good results in the spread of the coronavirus into the baby's body. IgA reactivity has a higher concentration than other cells. In conclusion, Covid-19 pandemic made the public worried about their health, including breastfeeding mothers. The role of health workers is needed to provide information related to breastfeeding exclusively to their babies so that they will receive protection against virus entered their bodies. Suggestion: It is necessary to develop studies regarding the typical responses that come up from IgA, IgM, IgG and are able to protect infants from Covid-19 and vertical transmission between mother and her baby during pregnancy to breastfeeding.